Elastoplastic time history analysis of reinforced engineered cementitious composite or engineered cementitious composite–concrete composite frame under earthquake action. Issue 4 (April 2017) - Yuan, Fang; Pan, Jinlong; Leung, Christopher KY
Engineered cementitious composite is a class of high-performance cementitious composites with pseudo-strain hardening behavior and excellent crack control capacity. Substitution of concrete with engineered cementitious composite can greatly reduce the cracking and durability problems associated with low tensile strength and brittleness of concrete and can significantly increase structural seismic resistance. In this article, a pair of beam–column joints with various matrix types has been tested under reversed cyclic loading to study the effect of substitution of concrete with engineered cementitious composite in the joint zone on the seismic behaviors of composite members. After that, a simplified constitutive model of engineered cementitious composite under cyclic loading is proposed, and the structural performance of steel reinforced engineered cementitious composite members is simulated by fiber beam elements. The accuracy of the model is verified with test data. Finally, three frame structures with different matrixes subjected to earthquake actions were numerically modeled to verify the contribution of ductile engineered cementitious composite material to structural seismic resistance. The seismic responses or failure mechanisms, deformation patterns, and energy dissipation capacities for each frame structure are analyzed and compared. The simulation results indicate that the application of engineered cementitious composite can reduce the maximum story drift ratio, and the distributions of the dissipated energy are more uniform along the building height when engineered cementitious composite is strategically used in ground columns and beam–column joints of the frame structure. The seismic performance of the reinforced engineered cementitious composite-concrete composite frame is found to be even better than the frame with all concrete replaced by engineered cementitious composite.